Daño hepático crónico como manifestación de pericarditis constrictiva. Reporte de un caso - Ugalde P., Héctor; Sanhueza F., María Ignacia; Yubini L., María Cecilia; Rozas A., Sebastián; Mundnich B., Stefanie; Cereceda B., Mauricio; Ramos G., Cristóbal (Revista Hospital Clínico Universidad de Chile, 2015)
Constrictive pericarditis (CP) is an uncommon condition which clinical presentation becomes very unspecific, making its diagnosis a hard challenge. It has multiple and varied causes, all of them determine pericardium inflammation and progressive fibrosis that restricts heart filling and develops diastolic dysfunction, expressing mainly as right heart failure. Symptoms of this last condition allow posing different diagnosis as they can appear in many other diseases, including chronic liver disease as happens in the following clinical case. A 27 year-old male patient with a history of progressive edema on his extremities, increased abdominal volume, a 3-month body weight loss, and dyspnea; is firstly diagnosed as CLD after medical evaluation. However, etiological studies for CLD appear negative and the patient does not respond to general approaches, motivating his hospitalization for further studies. Cardiologic tests reveal pulmonary hypertension, which is studied by MRI showing a thickened pericardium suggesting constriction that is confirmed by cardiac catheterization. The patient undergoes surgery without incidents and a favorable post-operatory period, being completely asymptomatic 3 months later. This clinical case reflects how difficult can become diagnosing CP; as well as presenting the right way to study these patients in order to confirm this alternative diagnosis, the treatment of choice, and the excellent results that surgery can achieve. Finally, CP is a rare condition that must be included within differential diagnosis of patients with clinical manifestations of RHF.